2017
DOI: 10.1016/j.amepre.2016.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Prevention Research Center Collaborations With State Departments of Health: Washington State

Abstract: State health departments and Prevention Research Centers (PRCs) have complementary mandates and expertise important to improving population health. State health departments manage and administer numerous programs with broad population reach. PRCs bridge dissemination and implementation research and public health practice to improve health programming and outcomes. This paper describes the 15-year partnership between the Washington State Department of Health and the PRC at the University of Washington. Through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The higher rate of use that we found could reflect the selection of LHDs included in the 2017 LHD survey, as it includes only LHDs that implement community health programs for chronic disease prevention. Hannon et al found that only about half of cancer control practitioners they surveyed had ever used an evidence-based practice resource such as the Guide ( 14 ). Brownson et al found that 90% of SHD participants were aware of the Guide, which was similar to our finding that 87% of SHD participants were aware ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The higher rate of use that we found could reflect the selection of LHDs included in the 2017 LHD survey, as it includes only LHDs that implement community health programs for chronic disease prevention. Hannon et al found that only about half of cancer control practitioners they surveyed had ever used an evidence-based practice resource such as the Guide ( 14 ). Brownson et al found that 90% of SHD participants were aware of the Guide, which was similar to our finding that 87% of SHD participants were aware ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that LHDs engaged in academic collaborations were more likely to report supports for the use of evidence-based decision making and more likely to implement EBIs than LHDs not engaged in such partnerships ( 19 ). Recent studies demonstrated successful formal and informal collaborations between academic institutions and SHDs or LHDs ( 14 , 19 ). Like partnerships, academic collaborations may allow health departments to fill gaps in expertise and resources that the departments themselves may not have.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations